2007
DOI: 10.1080/17477160701520165
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity are rapidly emerging among adolescents in Ho Chi Minh City, Vietnam, 2002–2004

Abstract: The prevalence of overweight and obesity among adolescents in Ho Chi Minh City is increasing rapidly. There is an urgent need to implement strategies for prevention and control amongst the adolescents of Ho Chi Minh City and other urban areas in Vietnam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 45 publications
5
30
5
Order By: Relevance
“…When the IDF, Cook and the De Ferranti definitions were applied, we found that the prevalence of MetS was higher in Vietnamese adolescents than that reported for adolescents in Hong Kong (Kong et al, 2008), South Korea (Park et al, 2009), China (Li et al, 2008;Yi-Qun and Cheng-Ye, 2008), and India (Singh et al, 2007). The high prevalence of MetS among adolescents in our study may be because the sample investigated came from a setting where there have been rapid changes in socio-economic status and lifestyles which resulted in increases of overweight/obesity and decreases of physical activity (Hong et al, 2007;Trang et al, 2012), while national samples were used in other Asian studies (which included both urban and rural populations). The factor analysis showed that obesity could explain the highest proportion of metabolic components confirming the strong association between obesity factor and MetS and the important role of this factor in MetS, as consistently seen in other studies (Ghosh, 2007;Ng et al, 2007).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…When the IDF, Cook and the De Ferranti definitions were applied, we found that the prevalence of MetS was higher in Vietnamese adolescents than that reported for adolescents in Hong Kong (Kong et al, 2008), South Korea (Park et al, 2009), China (Li et al, 2008;Yi-Qun and Cheng-Ye, 2008), and India (Singh et al, 2007). The high prevalence of MetS among adolescents in our study may be because the sample investigated came from a setting where there have been rapid changes in socio-economic status and lifestyles which resulted in increases of overweight/obesity and decreases of physical activity (Hong et al, 2007;Trang et al, 2012), while national samples were used in other Asian studies (which included both urban and rural populations). The factor analysis showed that obesity could explain the highest proportion of metabolic components confirming the strong association between obesity factor and MetS and the important role of this factor in MetS, as consistently seen in other studies (Ghosh, 2007;Ng et al, 2007).…”
Section: Discussioncontrasting
confidence: 81%
“…It is becoming a growing public health issue (Zimmet et al, 2007a), especially in developing countries, where the prevalence of chronic diseases is rising far more rapidly in comparison to developed nations (Yusuf et al, 2001). In Vietnam, adolescent obesity is emerging as an important health problem (Hong et al, 2007); however, there is no report of MetS in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted in 2004, which used International Obesity Taskforce (IOTF) cutoffs, the prevalences of overweight and obese adolescents in HCMC were 11.7% and 2.1%, respectively. A cross-sectional study in 2002 reported a prevalence of overweight and obesity among adolescents of HCMC of 5.9% and 0.7% [9]. These results demonstrate the high increase of overweight and obesity in adolescents from HCMC over two years.…”
Section: Introductionmentioning
confidence: 76%
“…Previous papers based on the cross-sectional baseline survey have described overweight and obesity,3 26 physical inactivity22 and metabolic syndrome27 and associated risk factors. Another paper has used the longitudinal data from the youth cohort to describe changes in active commuting to school and risk factors for changes in commuting status 28.…”
Section: Resultsmentioning
confidence: 99%